KAJIAN YURIDIS PENETAPAN PERMOHONAN ISBAT NIKAH DI PENGADILAN AGAMA WATAMPONE KELAS I.B - nurhidayah, Nurhidayah (Institut Agama Islam Negeri Bone, 2021)
The number of application on marriage legalization in the last two years in the Religious Watampone Class I.B has been quite high. This is due to the high demands of people to legalize their marriage for certain reasons, such as divorce proceedings for an undocumented marriage, administrative requirements to get children’s birth certificate, TASPEN (retirement funds) administration, passport registration, getting veteran widow's pension, and publication ofmarriage certificate due to underhand marriage.Regarding the marriage legalization cases in the Religious Court Class I.B of Watampone, if the formal requirements have been met, then the religious court by the judges will make a verdict or decision of which written